Counterterrorism and threat finance analysis during wartime - Blum, David; Conway, J. Edward (Lexington Books, 2015)
This book details the intellectual and bureaucratic challenges that intelligence analysts disrupting terrorist and insurgent finances encounter. Each chapter uses analytic methods via a case study drawn from the real experiences of intelligence analysts deployed to Iraq and/or Afghanistan to support live military operations